Modelo de adopción de tecnologías relacionadas con la web 2.0 para mejorar inteligencias múltiples en el nivel de básica elemental y media - Erazo Molina, Paulina Mercedes (2020)
The research theme revolves around the insufficient use and management of new technologies in the teaching-learning process of the subjects that make up the Basic Education Curriculum from third to fifth year, by the teachers of the Patria Fiscal Educational Unit of the Latacunga canton, mainly due to lack of knowledge, due to the scarce training they receive on the subject, and it is necessary to contribute with a methodological proposal that facilitates teachers, the integration of ICT into the teaching-learning process, which in turn constitutes a focused tool to develop multiple intelligences in children, for the strengthening of their abilities and talents. Web 2.0 tools are an alternative to boost children's learning, as well as tools that can help enhance multiple intelligences. In this sense, the general objective is to develop a methodological proposal for the use of web 2.0 tools to strengthen multiple intelligences, which may favor the types of intelligence proposed by Gardner (1987), for which reason it was taken as a point of starting, the scientific theoretical foundation of web 2.0 tools and their use in the training and development of multiple intelligences, diagnose the elements and levels corresponding to multiple intelligences in educational agents that allow identifying the types of intelligence that each of them possess , as well as teachers, to characterize their work methodology. Finally, the phases of the methodological proposal were established (three phases: identification of macro skills, selection of learning environments and Web 2.0 tools for each type of intelligence) and validation of the proposal based on expert judgment. As relevant conclusions and results, it was possible to demonstrate that web 2.0 tools allow strengthening skills and competences in students, so they can contribute significantly to strengthening multiple intelligences.